COMBINED TECHNOLOGY OF THE PROCESS OF GAS NITRIDING WITH SUBSEQUENT OXIDATION IN WATER VAPOR OF LOW- AND MEDIUM-CARBON STEELS - Sh. A. Berdiev (Web of Journals Publishing, 2025)
Increasing the corrosion resistance of a large number of metal products made from ordinary quality steel and ordinary low-carbon steel, from low-alloy structural steels, as well as rolling obtained by industrial smelting, made from structural steels and operating under low contact loads in conditions of atmospheric corrosion can be achieved by a combined low-temperature nitriding process.
Keywords: Ferrite, pearlite, nitriding, oxidation, diffusion coating, nitride layer, corrosion resistance.